Examining the Effectiveness of Spirituality-Oriented Psychological Counseling on Test Anxiety Components and Problem-Solving Skills in Female Junior High School Students - Bahari , Soheila; Hosseininasab , Seyed Davoud; Azmodeh , Masoumeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to determine the effectiveness of spirituality-oriented psychological counseling on test anxiety components and problem-solving skills in female junior high school students in District 3 of Tabriz.Methods and Materials:  The research method was quasi-experimental with a pre-test, post-test, control group, experimental group, and follow-up period design. The statistical population of the study included all female junior high school students in District 3 of Tabriz, totaling 8,256 students across 30 schools. From these schools, two were randomly selected, and 20 students from each school were voluntarily chosen as the research sample. To measure test anxiety, the Spielberger Anxiety Inventory was used, while the Heppner and Petersen Problem Solving Inventory was employed to assess problem-solving skills. For the intervention, Galanter and Siegel's spirituality therapy package was utilized. Multivariate analysis of variance (MANOVA) and the Bonferroni post-hoc test were used to analyze the research hypotheses.Findings: The results indicated that spirituality-oriented psychological counseling is effective and enduring on the components of test anxiety and problem-solving skills in female junior high school students.Conclusion: The findings indicate that spirituality-oriented psychological counseling effectively reduces test anxiety and enhances problem-solving skills in female junior high school students. These effects are sustained over time, highlighting the potential of this intervention for long-term benefits in managing anxiety and improving cognitive abilities among adolescents.